Estimation of diffusion modelling of unhealthy nanoparticles by using natural and safe microparticles - Ali Amarlou; Mario Coccia (Nanochemistry Research)
In this study, we evaluated aerosol transmission of two wild edible mushrooms. They were Calvatia booniana and was Terfezia claveryi Chatin with the spore sizes of about 1 to 2 µm and 20 µm, respectively. First, we stained both types of spores and carefully recorded the morphological shape of the two microparticles, which were different in size and cytological characteristics under an optical microscope.  We pumped the solution containing both large and small spores in tunnels of 3 x 3 x 3 cubic centimeters and 10 meters long. After half an hour we examined the presence and frequency of spore particles settling on the glass placed under the microscope. Based on the results, the larger micro particles with the diameter of 20 µm can diffuse about 60 to 70 cm, while small microparticles (2 µm) were spread about 200 cm. Since the COVID-19 is about 100 nano meters in size and assumes a direct ratio of size with the particle mass (m), using the classical kinetic energy formula (½ mv2), we estimated its diffusion more than 8-9 meters in room air condition.  Thus, the results indicate that it is highly important to know that the Coronavirus 2019 and similar viral agents spread through air more than 8-9 meters; therefore, appropriate control measures should be applied to prevent the diffusion of the SARS-CoV-2 and similar epidemics.